الضغط النفسي المدرك و علاقته بأساليب التعامل لدى الأطباء و الممرضين في زمن جائحة كوفيد-19 . - صيفي, فيصل; بحري, نبيل (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
هدفت الدراسة الحالية إلى الكشف عن طبيعة العلاقة بين مستوى الضغط النفسي المدرك و أساليب التعامل لدى الأطباء و الممرضين في زمن جائحة كوفيد-19. اعتمادا على المنهج الوصفي، تم استخدام مقياس الضغط النفسي المدرك لكوهين، و مقياس أساليب التعامل لبولهان لجمع البيانات من عينة عشوائية شملت 126 من أطباء و ممرضي المستشفى الجامعي بقسنطينة. حيث أظهرت الدراسة على عدم وجود علاقة دالة إحصائيا بين مستوى الضغط النفسي المدرك و أساليب التعامل المرتكزة على المشكلة، و وجودها بين مستوى الضغط النفسي المدرك و أساليب التعامل المرتكزة على الانفعال. The current study aimed to explore the relationship between the level of perceived stress and coping styles among physicians and nurses working at teaching hospital of Constantine during Covid-19 pandemic. Adopting a descriptive method, the data were collected using the Perceived Stress Scale of Cohen and Coping styles scale of Paulhan, from a random sample of 126 physician and nurse from the University Hospital of Constantine. This study showed no significant correlation between perceived stress level and problem focus coping style, and a significant positive correlation between perceived stress level and emotion focus coping styles.